Gender Discrimination - Kailing Shen (Institute of Labor Economics (IZA), 2021)
This chapter provides a bird's eye view of the literature on gender discrimination. The presentation of studies is grouped into five parts. Part 1 presents evidence of gender discrimination measured via various dimensions in various countries and contexts. Part 2 discusses in detail the gender wage gap—one of the most important measures of gender discrimination—as well as gender segregation and its origins. Part 3 discusses the close relationship between female empowerment and violence, and the experience of women of color. Part 4 covers gender behavioral differences. Part 5 presents studies on the experience of women trying to break the glass ceiling, as well as the differential effects of education on boys and girls.
Keywords: J16; J12; J13; 330; gender discrimination; gender wage gap; female empowerment; domestic violence; gender behavioural differences